3D bioprinted drug-resistant breast cancer spheroids for quantitative in situ evaluation of drug resistance. (15th January 2022) - Hong, Sera; Song, Joon Myong
Abstract: Drug-resistant cancer spheroids were fabricated by three-dimensional (3D) bioprinting for the quantitative evaluation of drug resistance of cancer cells, which is a very important issue in cancer treatment. Cancer spheroids have received great attention as a powerful in vitro model to replace animal experiments because of their ability to mimic the tumor microenvironment. In this work, the extrusion printing of gelatin-alginate hydrogel containing MCF-7 breast cancer stem cells successfully provided 3D growth of many single drug-resistant breast cancer spheroids in a cost-effective 3D-printed mini-well dish. The drug-resistant MCF-7 breast cancer spheroids were able to maintain their drug-resistant phenotype of CD44 high /CD24 low /ALDH1 high in the gelatin-alginate media during 3D culture and exhibited higher expression levels of drug resistance markers, such as GRP78 chaperon and ABCG2 transporter, than bulk MCF-7 breast cancer spheroids. Furthermore, the effective concentration 50 (EC50 ) values for apoptotic and necrotic spheroid death could be directly determined from the 3D printed-gelatin-alginate gel matrix based on in situ 3D fluorescence imaging of cancer spheroids located out of the focal point and on the focal point. The EC50 values of anti-tumor agents (camptothecin and paclitaxel) for apoptotic and necrotic drug-resistant cancer spheroid death were higher than those for bulk cancer spheroid death, indicating a greater drug resistance. Statement of significance: This study proposed a novel 3D bioprinting-based drug screening model, to quantitatively evaluate the efficacy of anticancer drugs using drug-resistant MCF-7 breast cancer spheroids formed within a 3D-printed hydrogel. Quantitative determination of anticancer drug efficacy using EC50, which is extremely important in drug discovery, was achieved by 3D printing that enables concurrent growth of many single spheroids efficiently. This study verified whether drug-resistant cancer spheroids grown within 3D-printed gelatin-alginate hydrogel could maintain and present drug resistance. Also, the EC50 values of the apoptotic and necrotic cell deaths were directly acquired in 3D-embedded spheroids based on in situ fluorescence imaging. This platform provides a single-step straightforward strategy to cultivate and characterize drug-resistant spheroids to facilitate anticancer drug screening. Graphical abstract: Image, graphical abstract